Two nations in Canada: the New Democratic Party, the Waffle movement and nationalism in Quebec. Issue 1 (March 2017) - Lexier, Roberta
Abstract : This article examines the influence of the Waffle movement, a short-lived attempt by members of the New Democratic Party (NDP) to shift the party to the left, on discussions about Quebec separatism. The Waffle pushed the NDP on policies related to Quebec nationalism in the late 1960s and early 1970s at a time when nationalist sentiment was growing among Quebeckers. Waffle members argued that the NDP should recognise that Canada comprised two distinct nations and that alliances could be created among socialists in English and French Canada that could advance Canadian nationalism. However, they also insisted that Quebec had the right to self-determination and should be allowed to separate if it was the will of the people. The NDP has long struggled with the national question and, while the Waffle existed for only a short time, it made an important contribution to ongoing debates within the party around this issue.